THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ON AFFECTIVE ORGANIZATIONAL COMMITMENT: THE MEDIATING EFFECTS OF INTRINSIC MOTIVATION, PROCEDURAL JUSTICE & TRUST - Shabrina Haya Zahradila; Fanny Martdianty (RADJA PUBLIKA, 2026)
Today, corporate social responsibility has become a widely recognized phenomenon, as different sentiments arise from various parties. It has been found that corporate social responsibility fosters many benefits, as it can alter a company’s blueprint not only externally but also internally. This research examines whether there is a relationship between employees’ perceptions of corporate social responsibility and affective organizational commitment, with intrinsic motivation, procedural justice, and employee trust mediating this relationship. This study was a quantitative design with 231 respondents participating in an online questionnaire. Respondents were employees from various industries who had worked for at least 1 year at their organizations. The data were analyzed using Structural Equation Modelling (SEM). The study found that corporate social responsibility has an indirect effect on affective organizational commitment through intrinsic motivation and employee trust. On the other hand, procedural justice is found to have no mediating relationship with the construct.